MicroRNA-155-5p Overexpression in Peripheral Blood Mononuclear Cells of Chronic Lymphocytic Leukemia Patients Is a Novel, Independent Molecular Biomarker of Poor Prognosis. (31st December 2017) - Papageorgiou, Sotirios G.; Kontos, Christos K.; Diamantopoulos, Marios A.; Bouchla, Anthi; Glezou, Eirini; Bazani, Efthymia; Pappa, Vasiliki; Scorilas, Andreas
Abstract : MicroRNA-155-5p (miR-155-5p) is a proinflammatory, oncogenic miRNA, involved in various physiological processes, including hematopoiesis, immunity, inflammation, and cell lineage differentiation. It regulates important transcription factors, such as E2F2, hypoxia-inducible factor 1 (HIF1), and FOXO3. Recently, the dysregulation of miR-155-5p expression has been linked to chronic lymphocytic leukemia (CLL) pathogenesis. In this research study, we investigated the potential diagnostic and prognostic value of miR-155-5p in CLL. To achieve our goal, we isolated total RNA from peripheral blood mononuclear cells (PBMCs) collected from 88 CLL patients and 36 nonleukemic blood donors and performed polyadenylation of total RNA and reverse transcription. Next, we quantified miR-155-5p levels using an in-house-developed real-time quantitative PCR method, before proceeding to extensive biostatistical analysis. Thus, it appears that miR-155-5p is significantly overexpressed in PBMCs of CLL patients and can distinguish them from nonleukemic population. Kaplan-Meier OS analysis and bootstrap univariate Cox regression showed that high miR-155-5p expression predicts inferior OS for CLL patients (p < 0.001 ). Interestingly, miR-155-5p overexpression retains its unfavorable prognostic role in CLL patients stratified according to established prognostic factors [CD38 expression and mutational status of the immunoglobulin heavy chain variable region ( IGHV )]. Thus, miR-155-5p appears as a promising, independent molecular biomarker of unfavorable prognosis in CLL.